PENGARUH KOMPENSASI, INSENTIF, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. CIPTA AGRO SEJATI, ROKAN HILIR, RIAU - Jessino, Erick; Simanjuntak, Demak Claudia Yosephine (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
Conducting tests by analyzing the influence of compensation, incentives and leadership styles on employee performance at PT. Cipta Agro Sejati, Rokan Hilir, Riau is the objective of this research. The decline that occurs in employee performance can be assessed from the achievement of company targets, which is caused by unsatisfactory compensation and incentives and ineffective leadership. The research method uses quantitative. The population taken by the researcher is 196 employee subjects and the sample used is 32 employees. Sampling random sampling is the sampling technique used. In calculating the hypothesis test obtained individually, the value of tcount> ttable or 3.887> 1.979 is obtained from the significance that is obtained 0.0¬00 <0.05, meaning that Ha accepted while Ho was rejected, namely by individual Compensation had a significant positive effect on the Employee Performance of PT. Cipta Agro Sejati, Rokan Hilir, Riau. The results in calculating the hypothesis test with individuals and simultaneously Compensation, Incentives, and Leadership Style have a significant positive effect on the Employee Performance of PT. Cipta Agro Sejati, Rokan Hilir, Riau.